Chebyshev-Gauss Approximation Analysis for Mobile Edge Computing-Aided IoT Networks. (18th July 2022) - Zhu, Fusheng; Chen, Liming; Zhou, Wen; Deng, Dan; Tang, Yajuan; Liu, Jun; Zhang, Yuwei; Cui, Tao; Zhang, Lin; Wang, Jing; Li, Sun
Abstract : Recently, mobile edge computing (MEC) has been widely applied into Internet of Things (IoT) networks, which has attracted a lot of attention from researchers. A critical challenge in the MEC-aided IoT networks is that the performance analysis is often complicated, where it is quite difficult for us to obtain some analytical or closed-form solution to the performance analysis, such as outage probability and bit error rate. This has been the bottleneck of the development of MEC-aided IoT networks. To address this challenge, we deeply investigate the Chebyshev-Gauss approximation method and derive the analytical solution to implement this powerful and useful approximation. We then give several examples to show the effectiveness of the Chebyshev-Gauss approximation in the performance analysis for the MEC-aided IoT systems. The results in this work can serve as an important reference and reveal some important inherent mechanisms for the MEC-aided IoT networks.